Mekanisme tata kelola dan pengungkapan tanggung jawab sosial perusahaan - Yoremia Lestari Ginting (KINERJA, 2016)
The objective of this research is to study and to gain empirical evidence in solving problem identification concerning “the effect of corporate governance mechanism (institutional ownership, managerial ownership, independent commissioners, and audit committee) toward CSR disclosure”. The sample of the study consist of 120 financial reports and annual reports in manufacturing sector that listed in the Indonesian Stock Exchange since 2007-2014.  The results of this research showed that the mechanism of corporate governance (institutional ownership, managerial ownership, independent commissioners, and audit committee) have a significant impact on CSR disclosure variable. Meanwhile, partially, only the variable managerial ownership and independent commissioners have the significant effects toward the disclosure of CSR.Keywords : institutional ownership, managerial ownership, independent commissioners, audit committee, CSR disclosure